The COMPARISON OF BUY AND HOLD VS MACD SIGNALS, PROFIT MAXIMIZATION ON FINANCE SECTOR STOCKS - Deara Shinta Lestari; Ryan Hasianda Pasaribu (JPIM (Jurnal Penelitian Ilmu Manajemen), 2024)
This study examines the performance of two investment strategies, the Buy & Hold strategy and the MACD strategy, using data from 20 stocks in the Indonesian capital market over a six-year period. The results show that while the Buy & Hold strategy generally generates higher returns, the MACD strategy offers more stable returns and lower losses in certain cases. Statistical analysis using the Mann-Whitney U test showed no significant difference between the two strategies, but the Buy & Hold strategy outperformed MACD by 11.2% in terms of average return, indicating that it performed better than MACD strategy.